A indústria da construção: uma análise das abordagens teóricas – segurança/saúde, qualidade, produtividade, treinamento, cultura, imigração e suas práticas nas empresas de médio porte - Maia, Valéria de Andrade (2020)
Construction Industry is considered one of the largest sectors of the world economy and the advent of global economic crises and technological advances have driven changes in its production chain. The sector, including Brazil, has undergone major transformations that have followed global trends in the era of globalization and the opening of borders. This Industry is undergoing reframing and the most recurrent approaches are: security, productivity, training, health, immigration, quality and culture. This work is an exploratory, explanatory and descriptive basic research whose main objective is to analyze the main theoretical approaches related to the Construction Industry, buildings sub-sector, and their practices in medium-sized companies in civil construction, in João Person / PB. One of the methodological procedures adopted was a systematic review of the literature carried out in five consecutive phases that aim to ensure rigor and transparency of the method. The results of this review were listed and discussed qualitatively through the classification process, systematic coding and identification of themes or standards. From the RSL, independent and dependent variables were identified that substantiate, by their significance, within the scope of the content of the research instrument, questionnaires, for carrying out multihull studies, carried out in 05 mediumsized local companies, through the application of questionnaires and visual inspection. The results showed that there are differences and similarities that are peculiar to issues of local economy and culture. These will serve as a basis for the adoption of strategies that meet and contemplate the wishes of the Construction Industry, providing better work and quality of life for its workforce.